Teacher Professionalism Development: Scientific Writing Training for Teachers in Madiun - Amita Tri Prasasti, Pinkan; Lukitasari, Marheny Lukitasari; Novi Primiani, Cicilia Novi Primiani; Handhika, Jeffry Handhika; Murtafiah, Wasilatul Murtafi’ah; Zahroatul Khoirotil Umath, Syamsiyatuz Zahroatul Khoirotil Umath; Khasanah, Qurul Khasanah (International Journal of Community Service Learning, 2022)
Writing scientific papers is a very important activity for a professional and competent teacher in their field. This activity does not only need to be carried out in order to obtain credit scores for promotions or for accreditation purposes, but also to increase the professionalism of teachers. The purpose of this activity is to assist teachers in the district Madiun in improving the professionalism of teachers by producing scientific publications based on the results of the preparation of CAR. The implementation of activities is carried out separately for each teacher with different educational levels. The training is carried out in a planned manner so as to support the goals set. In detail, the series of activities are described as follows: 1. Coordination of the community service team of FKIP UNIPMA with the Education Office of Madiun Regency; 2. The office sends a letter of assignment to the appointed committee and resource persons and determines the date of activities at each level; 3. The committee prepares administrative needs (correspondence, attendance), place of activity, contacting resource persons and providing supporting equipment to support activities; 4. Resource persons carry out activities according to the provisions. Based on the results of the mentoring, scientific papers from 60 participants at every level of kindergarten, elementary and junior high school education have been given recommendations by the team to be continued in scientific publications. All participants produced CAR and scientific articles. 20% of the total scientific articles have been published in scientific journals.